(3HSJGf GdCWHGA hQhVI GdCdHGAs - (3ehGab GdOjf CHj fUQ GSYO Hf GdjGS GHf GdeWQGf,J (B587 (3g` s
(3ChdgG (B:s
(3bGd GHf GdeWQGf Efi LGeY dfaSi ai cJGHi gPG JPGcQ eeG CWGdYg hGSeYg ef GdTjhN s
(3BNQgG (B:s
(3Cf GdeQVi CfeG ghGA bGd Mbjbi ddMQGQI hGdQWhHg hZPG bdfG ai GdeQV Efg dG GYJOGd Mbjbi adG jJhge s
(3BNQ UaMI cJHJ HNW eZGjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B243s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdWHs